The Existence of the Religious Court in Handling Divorce Cases on the Reason of Domestic Violence - Sumanto, Dedi; Samsudin, Titin; Amirudin, Fikri Hi. Asnawi (Jambura Law Review, 2021)
Domestic violence results in any action against a person in the household, which results in physical, sexual, psychological misery or suffering, and or neglect of the household, including threats to commit acts, coercion, or deprivation of liberty unlawfully within the household. The problem that arises is the legal perspective on domestic violence and the existence and role of the Religious Court in handling divorce cases on the grounds of domestic violence. This writing uses a normative juridical research method with a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials, then analyzed and drawn qualitative conclusions. The results of this study are in a review of Law Number 23 of 2004. Whatever its nature is, hitting the wife is one type of domestic violence prohibited by the PKDRT law. However, in essence, the law on domestic violence does not conflict with Islamic teachings because the law is made to protect the benefit of the community, namely protecting every member of the family or household from further acts of violence. The Religious Court has played an active role in applying the law in handling divorce cases on the grounds of domestic violence by applying the provisions of Article 39 paragraph 1 and paragraph 2 and the reasons for divorce in Article 19 of Government Regulation Number 9 of 1975.